Er en politisk skandale en politisk skandale? – danske medierede politiske skandaler i et komparativt perspektiv - van Dalen, Arjen; Skovsgaard, Morten (Politik, 2011)
Although media researchers, journalists and politicians across media systems agree that the mass media have the power to make or break politicians, types of scandals that are covered vary widely across countries. This article analyses the particularities of Danish mediated scandals by comparing them to scandal coverage in the United Kingdom, Spain and Germany. Based on a survey among political journalists in the four countries, the article presents differences in journalistic culture between the four countries by describing the dominant role conceptions. We argue that different role conceptions (watchdog, entertainment and political partisan) can all lead to scandal coverage, but that types of scandals vary across journalistic cultures along the dimensions breach of rules vs. breach of norms and public life vs. private life. Danish scandals coverage is most similar to German scandal coverage, with an emphasis on the watchdog role, little openly partisan scandal coverage (as in Spain), disapproval of the use ethically questionable reporting methods like wiretapping or opening garbage and reluctance to cover politicians’ sex life (as in the United Kingdom). The private life of Danish politicians is not completely off limits, but when the private life of politicians is broadly covered by Danish media, this is normally because politicians did not live up to the norms they set in public.